Chance discovery and scenario analysis for trend exploration on solar cell technology. (27th December 2010) - Chiu, Tzu-Fu
It is essential for managers and stakeholders to well understand the trends of a certain technology so that managers can enhance the performance of a company and stakeholders can make appropriate decisions for investment. Solar cell, one of renewable energies, is growing at a fast pace with its unexhausted and non-polluted natures. Meanwhile, the patent data contains plentiful technical information from which is worth exploring to extract further knowledge. Therefore, an integrated approach of chance discovery and scenario analysis has been proposed so as to analyse the patent data, to form the scenarios and to explore the trends of solar cell technology. Finally, the technical topics of solar cell have been realised, the relation patterns between topics have been identified, the scenarios and trends of each topic have been revealed and the tendency of overall situation have also been observed.